The Health Seeking Behaviors and Perceptions of Iranian Patient with Osteoarthritis about Pain Management: A Qualitative Study - Zamanzadeh, Vahid (J Caring Sci, 2017)
Introduction: Pain is the main reason for patients with osteoarthritis (OA) to visit health clinics. Health seeking behaviors indicate unmet patient needs and lack of understanding of OA pain patterns. This study aimed to describe the experiences of Iranian patients with OA and explore their health seeking behaviors and perceptions on pain management related to osteoarthritis. Methods: Using a qualitative approach, data was collected by interviewing 19 patients, 2 family members, and 5 health care providers from the in-patient and out-patient clinics, and physicians’ offices. Data saturation was reached after 31 in-depth and semi-structured interviews (five second interviews). Data were analyzed by qualitative content analysis, using comparison, reﬂection and interpretation techniques. The criteria used to enhance rigor included credibility, transferability, dependability, and conﬁrmability. Results: Two main categories and six subcategories emerged from data analysis. The first main category included "adapting to the reality" which had three subcategories: Facing OA pain, seeking health care, and accepting pain as a part of life. The second main category included "behavior fluctuation" with three subcategory of role conflict, responsibility for self-care and, adherence to prescribed treatment versus self-treatment. Conclusion: Care seeking behaviors for chronic pain sufferers are void of cultural, emotional, social and financial situation and patient expectations. Some misconceptions emerged about the health problem and its management, which may lead to negative attitudes toward treatment and therapists and finally lead to non-adherence to treatment. Patients need for education to enhance appropriate health care utilization.